Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1080/01431161003752430
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pre/post-fire differenced spectral indices for assessing burn severity in a Mediterranean environment with Landsat Thematic Mapper

Abstract: In this study several pre/post-fire differenced spectral indices for assessing burn severity in a Mediterranean environment are evaluated. Therefore GeoCBI (Geo Composite Burn Index) field data of burn severity were correlated with remotely sensed measures, based on the NBR (Normalized Burn Ratio), the NDMI (Normalized Difference Moisture Index) and the NDVI (Normalized Difference Vegetation Index). In addition, the strength of the correlation was evaluated for specific fuel types and the influence of the regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
1
18

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 39 publications
5
49
1
18
Order By: Relevance
“…The few studies in the California chaparral shrublands demonstrated that the NBR is reasonably well related to fire severity, however, none of them conducted an inter-indices comparison. In Mediterranean shrublands in Europe similar findings were obtained by De Santis and Chuvieco [18], Veraverbeke et al [32,33], Escuin et al [42] and Tanase et al [43]. Limited comparisons with other spectral indices were undertaken by De Santis and Chuvieco [18], Veraverbeke et al [32,33] and Escuin et al [42] concluding that the NBR outperformed the Normalized Difference Vegetation Index (NDVI) for assessing fire severity in Mediterranean shrublands.…”
Section: Introductionsupporting
confidence: 54%
See 3 more Smart Citations
“…The few studies in the California chaparral shrublands demonstrated that the NBR is reasonably well related to fire severity, however, none of them conducted an inter-indices comparison. In Mediterranean shrublands in Europe similar findings were obtained by De Santis and Chuvieco [18], Veraverbeke et al [32,33], Escuin et al [42] and Tanase et al [43]. Limited comparisons with other spectral indices were undertaken by De Santis and Chuvieco [18], Veraverbeke et al [32,33] and Escuin et al [42] concluding that the NBR outperformed the Normalized Difference Vegetation Index (NDVI) for assessing fire severity in Mediterranean shrublands.…”
Section: Introductionsupporting
confidence: 54%
“…In Mediterranean shrublands in Europe similar findings were obtained by De Santis and Chuvieco [18], Veraverbeke et al [32,33], Escuin et al [42] and Tanase et al [43]. Limited comparisons with other spectral indices were undertaken by De Santis and Chuvieco [18], Veraverbeke et al [32,33] and Escuin et al [42] concluding that the NBR outperformed the Normalized Difference Vegetation Index (NDVI) for assessing fire severity in Mediterranean shrublands. In addition, several authors indicated that the post-fire temperature increase as observed in the thermal infrared (TIR) domain [44,45] is complementary to the NBR for discriminating burned areas [46][47][48].…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…Despite low discrimination capabilities, NDMI and NBR are the best choice, while Wetness could offer a valuable support in shrublands starting from two years after the fires. In more vegetated areas such as broadleaved and needleleaved forests, fire scars are more persistent and NBR has often shown to perform better than in sparsely vegetated land [20,77]. From one to five years after the fire, the best SI are NBR and NDMI, followed by NDVI in broadleaved vegetation and BAIML in needle leaved vegetation.…”
Section: Summary Of Results Which Si Should We Choose?mentioning
confidence: 99%